Costly tolerance - Koffeman, Leo (HTS teologiese studies, 2016)
Tolerance is an aspect of the balance between power and freedom. This contribution starts from a decision taken by the general synod of the Reformed Churches in the Netherlands, in 1914, on the issue of church members who did not recognise infant baptism. The synod decided that – on certain conditions – ‘tolerance can be practiced’ towards such members. This contribution analyses and evaluates this decision, with particular attention for the distinction made between fundamental and non-fundamental faith issues. It shows how this decision is related to the broader context of early twentieth century political life in the Netherlands (the ‘Pacification of 1917’), and it concludes with some thoughts on the costliness of true tolerance.